Analytical Method for Polyelectrolytes in Sludge Condensation (Centrate) Units of a Wastewater Treatment Plant - Ozdemir, Aysun; Nuhoglu, Yasar (MDPI, 2025)
Polyelectrolytes (PEs) have a wide range of applications in various industrial processes, including water and wastewater treatment, cosmetics, and the textile industry. They remain irreplaceable as flocculants, particularly in wastewater treatment and sludge dewatering. Due to the variability in the pollutant parameters of wastewater over time, residual polyelectrolytes from the sludge dewatering process are inevitable. These residues can alter the physical and chemical properties of water, potentially causing an environmental hazard. Polyelectrolyte residues are a critical concern in wastewater treatment processes, and their concentration measurements represent one of the most essential steps in ensuring process efficiency. This study investigates the use of UV-VIS spectrophotometry to determine the concentrations of PEs used in water and wastewater treatment. The absorbance spectra of two different cationic polyelectrolytes (PEs) were tested in the wavelength range of 190-300 nm. A linear increase in absorbance values was observed with increasing polyelectrolyte concentrations, with R-2 > 0.99 at 190 nm wavelengths. The lowest detection limits were determined as 0.05 mg/L in distilled water and 0.085 mg/L in centrate water. For wastewater samples collected from sludge dewatering units, detection limits ranged from 0.08 mg/L to 0.013 mg/L, depending on the type of polymer. The method was successfully applied to determine polymer concentrations in centrate samples collected from two different wastewater treatment plants. It is thought that this study will assist in research on polyelectrolyte analysis in wastewater.
Keywords: polyelectrolyte; sludge dewatering; UV-VIS absorbance; detection limit; CATIONIC POLYELECTROLYTES; SOLUBLE POLYMERS; SURFACTANTS; Environmental Sciences & Ecology; Water Resources